Edad y crecimiento del híbrido de tilapia Oreochromis niloticus x Oreochromis aureus (Perciformes: Cichlidae) en la represa ?Zimapán? Hidalgo, México - A. Gómez-Ponce, M. (Universidad de Costa Rica, 2011)
Studies on age and growth in fishes are essential to establish models on population dynamics. The previos issues were determined in this study by scale growth analyses. Between September 2003 and May 2004, 382 organisms were captured using gill and atarraya nets. Eight samples were developed every month a long this study. Standard length in centimeters (Le), total weight in grams (Pt), scale length in centimeters (Lesc) and growth rings were determined. The size and weight ranged from 38 to 232mm (Le) and 8.7 to 311.9g (Pt), respectively. The growth rings analyses reveal four age groups, being the second group the most representative with 34.3% of the total sampled. The scale ring analyses showed two growth rings, one develops between November-January and the other between April-May, in good correlation with low temperature and gonad development, respectively. The growth parameters were established as: L??=281.1mm, W??=877.1g, K=0.33 and T0=0.88year-1. The growth curves based on length and weight were described by using the von Bertalanffy model: Le =28.11[1-e-0.33(t+0.88)] and Pt=877.17[1-e-0.33(t+0.88)]3. Finally, it is concluded that commercial catches in this dam are between a year and year and half-old when exploited.